Subcortical electrophysiological activity is detectable with high-density EEG source imaging - Martin Seeber (Nature Portfolio, 2019)
Electroencephalography (EEG) allows the measurement of electrical signals associated with brain activity, but it is unclear if EEG can accurately measure subcortical activity. Here, the authors show that source dynamics, reconstructed from scalp EEG, correlate with activity recorded from human thalamus and nucleus accumbens.